Komercdarbības veidi Latvijā un to īpatnības grāmatvedības uzskaites organizācijā - Mahte, Elvīra (Latvijas Universitāte, 2008)
Jauni uzņēmēji, kuri izlēmuši uzsākt patstāvīgu darbu un iekarot patērētāju simpātijas bieži apstājas izvēles priekšā, kādu komercdarbības veidu izvēlēties? Darba mērķis ir izpētīt sabiedrību ar ierobežotu atbildību un individuālo komersantu, to īpatnības grāmatvedībā un izstrādāt metodiku optimālākam komercdarbības veidam (SIA vai IK). Lai sasniegtu izvirzīto mērķi autors apskatīs komercdarbības veidus Latvijā, uz statistikas datu pamata analizēs mazu uzņēmumu attīstību Latvijā, to priekšrocības un trūkumus, izpētīs LR normatīvos aktus saistībā ar Sabiedrību ar ierobežotu atbildību un individuālo komersantu un to īpatnībām grāmatvedībā un izstrādās metodiku optimālākam komercdarbības veidam (SIA vai IK). Šo darbu var izmantot, lai plašāk iepazītos ar individuālāk komersanta un sabiedrības ar ierobežotu atbildību grāmatvedības organizāciju. Izstrādāto metodiku var izmantot, lai izvēlētos optimālāko komercdarbības veidu jaunam uzņēmējam.

Businesspeople who have decided to start their own business and gain consumers’ favour, often do make a pause before making their final choice. The question is: Which direction should they follow in the commercial business? The aim of this work is to look closer at Limited Companies and Individual Business, the peculiarities in the accounting, and to suggest methods for choosing the best direction in the commercial business. In order to achieve the aim of this work the author will have a closer look at different types of commercial business in Latvia. The development, advantages, and disadvantages of small enterprises in Latvia will be analysed based on the statistic data. The author will give a deep insight into the normative deeds of Latvia Republic in the connection with Limited Companies and Individual Business, and their peculiarities in the accounting. As a result, certain methods for an optimum choice of a type of commercial business will be provided. This research work can be used both for getting more information regarding the types and development of commercial business in Latvia and the accounting in Limited Companies and Individual Business. The methods which have been worked out in this paper can be applied for making an optimum choice regarding the types of commercial business.
Entreprioship Types in Latvia and their pecularities in accountancy
Keywords: Ekonomika